A case study: misconduct problem in a POS Malaysia Berhad / Nur Salafina Rabu Salim - Rabu Salim, Nur Salafina (Faculty of Business and Management, 2010)
The purpose of this study is about how to find a ways to avoid the employee to commit misconduct while serving in the Pos Malaysia Berhad. The employee that commits misconduct will create some losses and problem to the company. The main objective of this study is to know what the causes for the employee to commit misconduct that can give impact to the company performance and the corporate image of the company. The finding shows the cases of misconduct commit by the employee arise while they served for the Pos Malaysia Berhad and there are ways to maximize the problem or cases in order avoiding the misconduct from happen. The conclusion of this study was the outcome from the findings and recommendations for the alternative solution in order to avoid misconduct from happen.